Transformasi Dakwah : Pengaruh Perkembangan Zaman dalam Strategi Penyebaran Agama di Lingkungan Masyarakat - Hanifah Nur Aulia; Karina Aulia Putri; Marfa Azzahra Tyara Latifa; Nadya Amelia Putri Firman (STIKes Ibnu Sina Ajibarang, 2024)
Da'wah is a very essential part of a Muslim's life, where its essence lies in motivation, stimulation and guidance for others to accept the teachings of the Islamic religion with full awareness for their own benefit and not for the benefit of those who invite them. In an era that continues to develop, it influences challenges in preaching. Technological and environmental developments are the main factors in influencing the problems that occur in da'wah. In this modern era, social media and the internet are often used in everyday life. With this technology, there is a new opportunity for preachers to spread the teachings of the Islamic religion. However, this opportunity also poses challenges for preachers, such as poorly controlled information and the spread of information that is contrary to the truth. It is important for preachers to develop appropriate strategies and methods in delivering preaching material, adapting to using technology. Apart from technology, the environment influences people's views on preaching. People tend to think critically in receiving information about Islamic teachings. Therefore, preachers must have a strong understanding of social issues so that preaching runs smoothly. The strategies used by preachers must be clear and easy for the audience to understand. By adapting to the times, society really needs da'wah to provide benefits and solutions for life.